2022
DOI: 10.1183/23120541.00355-2022
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms persisting after hospitalisation for COVID-19: 12 months interim results of the CO-FLOW study

Abstract: IntroductionA large proportion of patients experiences a wide range of sequelae after acute COVID-19, especially after severe illness. The long-term health sequelae need to be assessed. Our objective was to longitudinally assess persistence of symptoms and clusters of symptoms up to 12 months after hospitalization for COVID-19, and to assess determinants of the main persistent symptoms.MethodsIn this multicenter prospective cohort study patients with COVID-19 are followed up for 2 years with measurements at 3,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Several symptoms (such as chest pain, sensory overload, and headache) could not be taken into account as they were added to this questionnaire in a later stage and contain incomplete data. 5 Dyspnea was assessed with the Modified Medical Research Council (mMRC) Dyspnea Scale, 32 the questionnaire scales the severity of dyspnea from 0 (no dyspnea) to 4 (severe dyspnea); scores ≥2 were considered representative for the presence of dyspnea symptom. The severity of fatigue was assessed using the FAS (score range 0-50) with a score ≥22 indicating substantial fatigue.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several symptoms (such as chest pain, sensory overload, and headache) could not be taken into account as they were added to this questionnaire in a later stage and contain incomplete data. 5 Dyspnea was assessed with the Modified Medical Research Council (mMRC) Dyspnea Scale, 32 the questionnaire scales the severity of dyspnea from 0 (no dyspnea) to 4 (severe dyspnea); scores ≥2 were considered representative for the presence of dyspnea symptom. The severity of fatigue was assessed using the FAS (score range 0-50) with a score ≥22 indicating substantial fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…Frequently reported symptoms are fatigue, impaired fitness, dyspnea, and cognitive impairment. 3-5 Numerous studies showed the presence of these symptoms beyond 3 months after acute severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, with evidence of persistence even two years after the acute illness. 6 As patients with long COVID differ substantially regarding symptoms, severity, and recovery profile, attempts have been made to discern different clinical phenotypes of long COVID, without reaching consensus to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant number of COVID-19 survivors report persistent taste disorders when followed up 1-12 months after symptom onset, disease diagnosis, or hospitalization [13,14]. The prevalence is 39% for dysgeusia at 8-month follow-up [11], 19% for ageusia at 12-month follow-up [15], and 22% for taste or smell impairment at 12month follow-up [16]. According to follow-up studies [11,17,18] and comprehensive symptom reviews [13,19], xerostomia, dry mouth, and hyposalivation persist in COVID-19 survivors with prevalence of 9-29% at 1-8 months follow-ups.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, aquatic exercise carried out in mineral-rich water seemed to add a protective effect on the microcirculatory system, in the lymph flow and in tissue metabolism. 14 Nevertheless, the lack of data in the literature on the effects of rehabilitation programs on medium-and long-term long COVID symptoms, 18,19 and the heterogeneity in durations and contents of the few existing studies, [20][21][22][23] determined the need for further investigations. Therefore, with this further analysis we aim to increasing knowledge on rehabilitation programs in patients with long COVID syndrome, evaluating also clinical outcomes in the long-term.…”
mentioning
confidence: 99%